The Status of Junior Pediatric Surgeons in Europe: Old Challenges, New Opportunities - Zani, Augusto (European Journal of Pediatric Surgery, 2017)
Despite the efforts to unite Europe under the same rules and regulations, for the medical profession, there are still big differences between the European countries in terms of type of postgraduate training, posttraining job opportunities, and the role that junior doctors have in the different health care systems. Junior pediatric surgeons face similar challenges to those of other junior doctors, especially those of junior surgeons in other specialties. The introduction of the European working time directive in 2003 has greatly reduced training hours and imposed a necessary change in the type of training that surgical trainees now receive: competency-based education, clinical teaching away from the patient, self-learning, on line tutorials, and simulation. There are many diverse training systems in pediatric surgery across Europe, with differences that include the duration of training, the existence of an exit exam at the end of training, and the exposure to adult and/or pediatric orthopaedic trauma. The European Board of Pediatric Surgery is not mandatory to practice pediatric surgery in Europe but would be a good tool to standardize training and practice across the continent. Despite the differences of training systems and regulations between the European countries, medical mobility of junior pediatric surgeons seeking better educational opportunities or careers is common. The European Pediatric Surgeons' Association has recently created the Group of Young Pediatric Surgeons of Europe, a platform for young pediatric surgeons younger than the age of 35 years. This platform will be helpful in addressing the challenges that European junior pediatric surgeons face.
Keywords: European working time directive; surgical training; medical mobility; competency-based education; Brexit